Dynamic modeling of a simple reverse osmosis desalination plant for advanced control purposes - Gambier, Adrián; Krasnik, Andrej; Badreddin, Essameddin (American Control Conference, 2007, 2007)
Reverse osmosis (RO) has become an important process for desalting water. It requires an efficient control system to maintain costs at acceptable level and therefore dynamic models are essential. Although it is possible to find in the literature steady-state models and some dynamic models obtained by parameter identification, there are no reports about lumped parameter dynamic models for control purposes obtained by application of physical laws. Such models are useful not only to design model-based control systems but also for the implementation of fault tolerant systems based on fault detection and isolation (FDI) methods, as well as to analyze transient characteristics of the plant. In this paper, models from the literature are shortly analyzed and a simple lumped parameter model for control purposes, which is derived from physical laws, is proposed. Moreover, a block-oriented library for MATLAB/SIMULINKtrade is presented, so that different plant configurations can be implemented as block diagram to simulate the system and to test control algorithms.